Evaluation of Retinal Nerve Fiber Layer Thickness in Acromegalic Patients Using Spectral-Domain Optical Coherence Tomography. (3rd May 2016) - Duru, Necati; Ersoy, Reyhan; Altinkaynak, Hasan; Duru, Zeynep; Çağil, Nurullah; Çakir, Bekir
ABSTRACT: Purpose : To evaluate retinal nerve fiber layer (RNFL) thickness in acromegalic patients. Methods : A study group of 29 patients with acromegaly and a control group of 38 age-matched healthy individuals were enrolled in a cross-sectional study. The study group was further divided by tumor size into two subgroups, a macroadenoma group and a microadenoma group. Serum growth hormone (GH) and insulin-like growth factor-1 (IGF-I) levels were detected at the time of ophthalmological examination in the study group. In both the study and control group, the RNFL thickness in the four quadrants was measured by optical coherence tomography. The relationship between GH and IGF-I levels and RNLF thickness was also evaluated. Results : The difference in mean RNLF thickness in all quadrants between the study and control groups was not statistically significant. In acromegalic patients with macroadenoma, the mean RNLF thickness of the inferior quadrant decreased significantly compared to both patients with microadenoma and healthy individuals ( p = 0, 032 and p = 0, 046). GH and IGF-1 levels were not significantly correlated with the RNLF thickness in the study group. Conclusions : Excessive GH and IGF-1 levels do not affect the optic nerve or RNLF thickness, whereas the RNLF becomes thinner in the inferior quadrant in acromegalic patients with macroadenoma as a result of the chiasmal compression.